Bioactive polyphenol profiling and in-vitro antioxidant activity of Tinospora cordifolia Miers ex Hook F and Thoms : A potential ingredient for functional food development (Bangladesh Journal of Scientific and Industrial Research, 2020)
Antioxidant activities and specific bioactive polyphenol content of methanol and ethanol extracts of the stem of Tinospora cordifolia Miers were evaluated in the present investigation. Phenolic compounds were identified by High Performance Liquid Chromatography (HPLC). Results revealed that absolute methanol extract had the lower IC50 value. DPPH (1, 1-Diphenyl-2-Picryl Hydrazyl) was scavenged 50% by 9.36±1.75 mg/ml methanol extract. Flavonoid, tannin and phenolic contents were found comparatively higher in methanol extract. The study implied that the methanol extract had higher antioxidant activity than the ethanolic extract and T. cordifolia stem can be used as a source of biologically active polyphenolic compounds as well as antioxidants to develop functional food.Bangladesh J. Sci. Ind. Res.55(1), 23-34, 2020